2011
DOI: 10.1055/s-0031-1300158
|View full text |Cite
|
Sign up to set email alerts
|

Neurosedative and Antioxidant Activities of Phenylpropanoids from Ballota nigra

Abstract: Ballota nigra is a European plant known for its neurosedative properties. In this study, the ability of five phenylpropanoids (verbascoside, forsythoside B, arenarioside, ballotetroside, and caffeoyl malic acid) isolated from a hydroalcoholic extract, to bind to benzodiazepine, dopaminergic, and morphinic receptors was investigated. To carry out these studies, affinity tests with rat striata, entire brains and receptor rich preparations were employed. In addition, the phenolic aspect of these five phenylpropan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…As far as phenylpropanoids usually found in Verbenaceae are concerned, verbascoside, 5, has already been tested on benzodiazepine receptors (Daels-Rakotoarison et al, 2000) and its IC 50 (1.9 mM) was compatible with the lack of effect at 300 lM, observed in the present study (Table 3). For the other phenylpropanoid tested here (compound 4) there is no previous data in the literature.…”
Section: Resultssupporting
confidence: 87%
“…As far as phenylpropanoids usually found in Verbenaceae are concerned, verbascoside, 5, has already been tested on benzodiazepine receptors (Daels-Rakotoarison et al, 2000) and its IC 50 (1.9 mM) was compatible with the lack of effect at 300 lM, observed in the present study (Table 3). For the other phenylpropanoid tested here (compound 4) there is no previous data in the literature.…”
Section: Resultssupporting
confidence: 87%
“…The extensive family of phenylpropanoids contains natural molecules that are water soluble, widely distributed in the plant kingdom and have been isolated from medical plants. In vitro studies have demonstrated that these molecules promote anti-inflammatory (Deepak and Handa, 2000), anti-tumour (Kunvari et al, 1999) and antioxidant (Daels-Rakotoarison et al, 2000) activities through a scavenger effect on reactive oxygen species (ROS; Wang et al, 1996;Gao et al, 1999). Many studies have also shown the antioxidant activity of verbascoside on cellular systems and on various organs and systems of the human body (Li et al, 1999;Chen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, a number of individual active compounds were isolated and identified. The following were purified from leaf extract (water/EtOH 1 : 1) of B. nigra collected in France [236,237]: (+)-(E)-caffeoyl-L-malic acid (186), verbascoside 227, forsythoside B (223), arenarioside (220), and ballotetroside (221). On the other hand, morin (110) and quercetin (100) were isolated from the bio-guided purification of the methanolic extract of O. persica [160].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…On the other hand, morin (110) and quercetin (100) were isolated from the bio-guided purification of the methanolic extract of O. persica [160]. In an interesting study [236], some chemical indicators of the intracellular inflammatory cascade reaction of the neutrophils were evaluated: superoxide anion, H 2 O 2 , HClO, and OH radical. All of the compounds were found to be active, inhibiting the development of oxygenated species to various degrees; only ballotertoside (221) was inactive in the superoxide anion and OH radical tests.…”
Section: Antioxidant Activitymentioning
confidence: 99%